Children's Healthcare During Corona Virus Disease 19 Pandemic: the Italian Experience. Issue 7 (July 2020) - Buonsenso, Danilo; Onesimo, Roberta; Valentini, Piero; Chiaretti, Antonio; Gatto, Antonio; Attinà, Giorgio; Conti, Giorgio; Vento, Giovanni; Cambieri, Andrea; Mercuri, Eugenio; Zampino, Giuseppe
Abstract : The unexpected outbreak of Corona Virus Disease 19 had several consequences worldwide and on the Italian Health System. We report our experience in the reorganization of our Pediatric Department to prevent the risk of infection for both children and staff. We strongly believe that the need to face an unpredictable emergency situation should not affect the quality of the assistance to the non–Corona Virus Disease patients.